Mineralogical and textural characterization for increased iron oxide recovery. Exemplified on the Storforshei iron formation - Tøgersen, Marte Kristine (Minerals Engineering, 2019)
Process mineralogy is increasingly becoming an important part of quality control in mining operations, and chemical assays are not sufficient for predicting metallurgical performance of complex ore deposits. Knowledge of mineralogical and textural ore properties that affect the mineral processing, may lead to better utilisation of the deposit, and the prediction of recovery becomes more solid. The Storforshei iron formation (IF) is located in the Dunderlandsdalen valley c. 30 km northeast of Mo i Rana, Nordland county, Norway. The IF consists of highly metamorphosed and deformed hematite-magnetite ore deposits and belongs to the Uppermost Allochthon (UmA) in the Norwegian Caledonides. Rana Gruber (RG) mines deposits in the Storforshei IF, where the main products are hematite concentrates for pellets and sinter production, with magnetite concentrates for pigment production and water purification as a by-product. The main production today is from the Kvannevann deposit, but several other deposits have been in production previously. The deposits in the Storforshei IF show mineralogical and textural differences, and in order to investigate the effects of these differences on the metallurgical performance, a pilot circuit was constructed based on the hematite production line in the fullscale mineral processing plant. The pilot circuit consisted of autogenous milling, wet low intensity magnetic separation (LIMS), and wet high intensity magnetic separation (WHIMS). Three deposits were sampled for testing in the pilot circuit, Kvannevann, Stensundtjern, and Stortjønna. The aim of the pilot circuit was not to fully replicate the full-scale mineral processing plant, but rather to discover differences in the metallurgical performance of the deposits. Six ore types were defined based on geological mapping and drill core logging from these three deposits, and their surface hardness were measured using Schmidt hammer and Equotip. The ore types are: Granular-Hematite, Specular-Hematite, Hematite-Magnetite, Magnetite-Ore, ...